The association of visceral fat metabolism score with hyperuricemia—evidence from NHANES 1999–2018 - Xie, Lin; Qu, Huali; Lai, Dandan; Li, Juan; Chen, Xushan; Xie, Jiajia (Frontiers in Nutrition, 2025)
ObjectivesDespite substantial evidence that visceral obesity is an epidemiological risk factor for hyperuricemia (HUA), studies on the connection between the Metabolic Score for Visceral Fat (METS-VF) and HUA remain insufficient. This research focused on METS-VF’s potential role as a risk factor for HUA.MethodsNotably, 8,659 participants from the National Health and Nutrition Examination Survey (NHANES) from 1999 to 2018 were enrolled in this study. Propensity score matching (PSM), multivariate logistic regression analysis, subgroup analysis, interaction test, and restricted cubic spline (RCS) analysis were implemented to identify the correlation between METS-VF and HUA.ResultsIn the fully adjusted model, the results of the multiple logistic regression analysis indicated that METS-VF was related to an elevated prevalence of HUA [before PSM: odds ratio (OR) = 3.51 (2.88, 4.27), p < 0.001; after PSM: OR = 2.90 (2.36, 3.58), p < 0.001]. In RCS analysis, a non-linear positive correlation was observed between METS-VF and the incidence of HUA (before PSM: p-non-linear <0.001; after PSM: p-non-linear = 0.0065). Subgroup analysis and interaction tests revealed that the impact of METS-VF on HUA was modified by sex and ethnicity.ConclusionThere is a significant positive correlation between METS-VF and HUA in adults in the United States. METS-VF could serve as a valuable metric for assessing the development and progression of HUA.